Three-dimensional Space Mechanics Analysis of Hexapod Robot with Electro-hydraulic Driven - Cheng Qian; Jiang Gang (Jixie chuandong)
A 3D model of hexapod robot leg mechanism is built,and the optimization problems of hydraulic design are discussed.Then its mechanics model is established.The output torque characteristics of robot each joint at steady state are obtained through the statics analysis,and the output torque characteristics of robot each joint in the process of movement are obtained by Lagrange method as an approach for the dynamics analysis.Finally,based on the dynamics analysis results,the foot trajectory and leg posture simulations of single leg mechanism are carried out by using ADAMS,and through the results,the smooth movement of the leg mechanism is verified and the theoretical support for the follow-up research is provided.